2017
DOI: 10.52041/serj.v16i2.200
|View full text |Cite
|
Sign up to set email alerts
|

A Flipped Classroom Model for a Biostatistics Short Course

Abstract: Effective pedagogical strategies are needed to improve statistical literacy within health sciences education. This paper describes the design, implementation, and evaluation of a highly interactive two-week biostatistics short course using the flipped classroom model in the United States. The course was required for all students at the start of a doctoral degree program with the goal of standardizing student preparation, contextualizing biostatistics to healthcare, and identifying students needing additional h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The statistical analysis confirmed a positive change in the ability to interpret statistical data, as well as the ability to critically evaluate the submitted statistical information. Both competencies are an essential element of statistical literacy [48]. After passing the post-test, up to 69% of students said that they understood the basic concept and principles of statistics (question 10).…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analysis confirmed a positive change in the ability to interpret statistical data, as well as the ability to critically evaluate the submitted statistical information. Both competencies are an essential element of statistical literacy [48]. After passing the post-test, up to 69% of students said that they understood the basic concept and principles of statistics (question 10).…”
Section: Discussionmentioning
confidence: 99%
“…The authors reason flipped classroom teaching promotes critical thinking, also makes the students feel more engaged. 14,15,16 Socio-cultural differences, racism and Flipped Classroom With the rise in globalization and increase in ease of travel, international students' population would increase. These international students face a lot of challenges in terms of acclimating themselves to the new social and cultural environment.…”
Section: Non-clinical Subjects Long Term and Short-term Impact Of Fli...mentioning
confidence: 99%
“…Flipped classrooms are applied in many different fields, but there have already been several examples in the field of statistics education. These studies [55,[57][58][59][61][62][63] examined the effect of the flipped classroom on student performance by using a control group which is a traditional classroom. Most of the studies found that a flipped classroom improves performance.…”
Section: Flipped Classroommentioning
confidence: 99%